Pengaruh Model Problem Bassed Learning (PBL) Terhadap Hasil Belajar Siswa Dalam Pembelajaran Pendidikan Kewarganegaraan - Afiola, Regina; Arwin, Arwin; Eliyasni, Rifda (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2016)
This research aims at finding out the effects of applying the Problem Based Learning (PBL) model toward the students’ learning outcomes of Civics subject at Class V of SDN 12 Tanah Sirah. The population of this quasi experiment research wass all 5th grade students of the school in which VA acted as the control class and VB as the experimental one. The research result shows that there are effects of applying the model toward the students’ learning outcomes. Based on the data analysis, it is found that tcount = -3.421 with P-Value of 0.001. Sice the score of the P-Value is lower than α = 0.05, the H1 hypothesis is accepted Keywords : the PBL Model, Learning Outcomes